2008
DOI: 10.1007/s00122-008-0755-x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and linkage disequilibrium analysis within a selected set of cultivated tomatoes

Abstract: Within the Dutch genomics initiative the "Centre for Biosystems Genomics" (CBSG) a major research eVort is directed at the identiWcation and unraveling of processes and mechanisms aVecting fruit quality in tomato. The basis of this fruit quality program was a diverse set of 94 cultivated tomato cultivars, representing a wide spectrum of phenotypes for quality related traits. This paper describes a diversity study performed on these cultivars, using information of 882 AFLP markers, of which 304 markers had a kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 35 publications
6
56
0
3
Order By: Relevance
“…cerasiforme is not recognized in the recent taxonomic revision of genus Lycopersicon into Solanum L. section Lycopersicon (Peralta et al, 2008) and may represent an admixture of S. lycopersicum and S. pimpinellifolium L. (Nesbitt and Tanksley, 2002). Cherry tomato cultivars were shown to be genetically distinct from beef and round tomato cultivars using amplified fragment length polymorphism markers (van Berloo et al, 2008). Only one accession in our panel was classified as cherry.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…cerasiforme is not recognized in the recent taxonomic revision of genus Lycopersicon into Solanum L. section Lycopersicon (Peralta et al, 2008) and may represent an admixture of S. lycopersicum and S. pimpinellifolium L. (Nesbitt and Tanksley, 2002). Cherry tomato cultivars were shown to be genetically distinct from beef and round tomato cultivars using amplified fragment length polymorphism markers (van Berloo et al, 2008). Only one accession in our panel was classified as cherry.…”
Section: Introductionmentioning
confidence: 85%
“…The majority of pairs of loci were in linkage equilibrium. Similarly, interlocus LD was rare in a study of European greenhouse tomato cultivars (van Berloo et al, 2008). In a study of Italian tomato landraces 0.04 of SSR loci pairs were in LD, mostly due to interchromosomal LD (Mazzucato et al, 2008).…”
Section: Neutrality Testsmentioning
confidence: 96%
See 2 more Smart Citations
“…The same data set, has been studied by Ursem et al (2008), van Berloo et al (2008a, where more details about the data and their preparation can be found.…”
Section: Data Descriptionmentioning
confidence: 99%